Microfluidic Logic Gates: Pressure‐Driven Two‐Input 3D Microfluidic Logic Gates (Adv. Sci. 2/2020) - El‐Atab, Nazek (Adv Sci (Weinh), 2020)
In article number https://doi.org/10.1002/advs.201903027, Muhammad M. Hussain and co‐workers demonstrate a multilevel microfluidics chip with different Boolean logic functions including AND, OR and XOR, in addition to a half adder microfluidic circuit based on a pressure‐driven approach. The developed methodology enables simple cascading of logic gates for large‐scale and complex microfluidic computing systems using any non‐functionalized fluid. [Image: see text]